Pengaruh Edukasi Peer Group terhadap Peningkatan Kepatuhan Konsumsi Tablet Tambah Darah pada Remaja Putri di SMA Negeri 1 Godean (Inovasi Kesehatan Global, 2026)
Adolescent girls' adherence to taking iron tablets is still lacking, iron intake is very important to prevent anemia. Based on the 2018 Riskesdas, the coverage rate of iron tablets is 76.2%, but the awareness of adolescent girls of the importance of preventing anemia by consuming iron tablets is still low. One way to increase compliance with taking blood supplement tablets is by utilizing peer group education. This study aims to determine the effect of peer group education in an effort to increase adherence to taking blood tablets for adolescent girls. This is a quantitative pre-experimental study using One-Group Pretest-Posttest Design. The population was all students of class XI SMAN 1 Godean. Simple random sampling technique with a sample size of 58 female students. Education time was 40 minutes with peer educators in each group. Data analysis using the Wilcoxon test with the results of compliance with iron tablet consumption before education in adolescent girls at SMA Negeri 1 Godean in the category of non-compliant as many as 51 people (87.9%) and compliant as many as 7 people (12.1%), compliance with iron tablet consumption after education has increased in the category of compliant as many as 16 people (27.6%) and non-compliant as many as 42 people (72.4%). In the Wilcoxon Test, the results obtained p = 0.013, therefore it was concluded that there was an effect of peer group education on increasing compliance with blood supplementation tablet consumption in adolescent girls of SMA Negeri 1 Godean.